2022
DOI: 10.1021/acsomega.2c05627
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Origin of Enhanced Electrochemical Oxygen Evolution Reaction Performance of 2H-Hexagonal Ba2CoMnO6−δ as a New Member in Double Perovskite Oxides

Abstract: Perovskite oxides have been considered promising oxygen evolution reaction (OER) electrocatalysts due to their high intrinsic activity. Yet, their poor long-term electrochemical and structural stability is still controversial. In this work, we apply an A-site management strategy to tune the activity and stability of a new hexagonal double perovskite oxide. We synthesized the previously inaccessible 2H-Ba2CoMnO6−δ (BCM) perovskite oxide via the universal sol–gel method followed by a novel air-quench method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…reported a series of A -site perovskites and found that Ba 2.4 CoMoO 6 exhibited improved OER activity with a low overpotential (423 mV). Other reports also show that Ba 2+ -based and -modified , perovskites are promising photocatalysts for water-splitting applications. Therefore, it is necessary to unveil other underlying physics of these compounds and explore viable Ba 2+ -based double perovskites for visible-light-driven photocatalysts.…”
Section: Introductionmentioning
confidence: 97%
“…reported a series of A -site perovskites and found that Ba 2.4 CoMoO 6 exhibited improved OER activity with a low overpotential (423 mV). Other reports also show that Ba 2+ -based and -modified , perovskites are promising photocatalysts for water-splitting applications. Therefore, it is necessary to unveil other underlying physics of these compounds and explore viable Ba 2+ -based double perovskites for visible-light-driven photocatalysts.…”
Section: Introductionmentioning
confidence: 97%
“…Following these, the subsequent peaks are indicative of oxygen vacancies. The initial peak at approximately 531 eV corresponds to OH – or O 2 , , which assumes paramount significance in the OER and ORR. Particularly, OH – functions as a pivotal species in OER, facilitating an interaction with active metal sites and leading to the formation of oxyhydroxide species, subsequently driving O 2 evolution.…”
Section: Resultsmentioning
confidence: 99%
“…The HEPO samples were synthesized by the modified sol–gel Pechini method, as mentioned in our previous research . Subsequently, after drying, the single-phase high-entropy perovskite oxides were obtained rapidly via joule heating of the nickel foam.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations